Tracking control of a mobile robot based on Taylor Formula - Rosales Acosta, Andrés (2007)
In this work, a strategy to calculate the control actions for a mobile robot following a pre-established trajectory is proposed. For this purpose, the Taylor series development of controlled variables is used and the control action is calculated to make the system follow the reference trajectory. As main result, an easy form to implement the strategy is obtained. Simulation and experimental results are presented, showing the advantages of the control strategy proposed.